All the days were summer - Bickham, Jack M. (New York : Doubleday & Company, Inc., 1981)
In the summer of 1943 as a 12 year old boy tries to cope with his dog's blindness and his father's new job with german prisoners of war, he finds his life unalterably changing.
Keywords: MOVING, HOUSEHOLD -- FICTION; DOGS -- FILIPINO; PRISONERS OF WAR -- FICTION